Exact Lyapunov Dimension of Attractors and Convergence for the Lorenz System - Leonov, G. A. (Journal of Applied Nonlinear Dynamics, 2026)
Lyapunov dimension formula for Lorenz system is obtained. The methods of attractors localization and Lyapunov functions are developed.